2020
DOI: 10.1029/2019tc005645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Dead Sea Transform Kinematics on Adjacent Volcanic Activity

Abstract: The Dead Sea Transform (DST) cuts through the northwestern edge of the Harrat ash Shaam volcanic field of western Arabia. The relation of the DST to adjacent volcanic activity has varied during the last 5 Ma. While Pliocene volcanism erupted on both shoulders of the DST and thick sections of volcanics accumulated along its axis, Pleistocene volcanic activity gradually abandoned the transform area while continued farther east. This was concomitant with the increase of transform-normal (E-W) contraction along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…This is further supported by Pico et al (2018Pico et al ( ), 2017Pico et al ( , 2016 who calculated the sea level to have 2003) (shifted for +5, +10, +15, +20, +25, +30 m) and comparison to the depth of the distant terrace sequence. The yellow points declare E-W contraction events and the activation of intense thrusting which is translated as uplifting events (Weinstein and Nuriel, 2019;Weinstein et al, 2020). (For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article.)…”
Section: "Distant" Submarine Terracestowards a Higher Mis3mentioning
confidence: 99%
See 1 more Smart Citation
“…This is further supported by Pico et al (2018Pico et al ( ), 2017Pico et al ( , 2016 who calculated the sea level to have 2003) (shifted for +5, +10, +15, +20, +25, +30 m) and comparison to the depth of the distant terrace sequence. The yellow points declare E-W contraction events and the activation of intense thrusting which is translated as uplifting events (Weinstein and Nuriel, 2019;Weinstein et al, 2020). (For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article.)…”
Section: "Distant" Submarine Terracestowards a Higher Mis3mentioning
confidence: 99%
“…However, the formation of the distant STs during the MIS 3 could be further supported by the regional tectonic activity which may have contributed to their preservation. U-Th datings from calcite-filled veins records in the Metulla block at the southern fringes of the Yammouneh fault (Weinstein and Nuriel, 2019;Weinstein et al, 2020), showed extensive growth of the veins from 53 to 16ka BP. This is tectonically translated to strong E-W contraction and activation of intense thrusting, which is responsible for the uplifting regime of our survey area.…”
Section: "Distant" Submarine Terracestowards a Higher Mis3mentioning
confidence: 99%
“…Some studies have revealed the temporal correlation between carbonate deposits like travertine beds and carbonate veins with volcanism (Karabacak et al, 2020(Karabacak et al, , 2017Priewisch et al, 2014;Weinstein et al, 2020). Priewisch et al (2014) and Karabacak et al (2017) associated travertine formation with volcanism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies asserted the temporal correlation between carbonate precipitation and volcanism with random sampling strategies on travertine deposits, veins and speleothems (e.g. Tuccimei et al, 2006;Priewisch et al, 2014;Karabacak et al, 2017;Weinstein et al, 2020). For example, Priewisch et al (2014) suggest that the deposition ages of voluminous travertines overlap with the episodes of basaltic volcanism in New Mexico and Arizona.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies asserted the temporal correlation between carbonate precipitation and volcanism with random sampling strategies on travertine deposits, veins and speleothems (e.g. Tuccimei et al ., 2006; Priewisch et al ., 2014; Karabacak et al ., 2017; Weinstein et al ., 2020). For example, Priewisch et al .…”
Section: Introductionmentioning
confidence: 99%